2022
DOI: 10.1155/2022/6830705
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Cotinine Levels and Bone Mineral Density: An Analysis of the National Health and Nutrition Examination Survey (NHANES)

Abstract: Purpose. To investigate the relationship between serum cotinine and lumbar bone mineral density (BMD) among 7905 participants aged 30 years and over. Method. A total of 3945 men and 3960 women from the National Health and Nutrition Examination Survey 2011–2018 were included in this cross-sectional analysis. Independent variable was serum cotinine, which is a biomarker of cigarette exposure. The outcome variable was lumbar BMD. We investigated the associations of serum cotinine levels and lumbar BMD using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Serum cotinine and the frequency of bone diseases were positively and nonlinearly correlated. Fang, et al also reported that high serum cotinine levels significantly reduced lumbar BMD participants aged 30 years or older [30].…”
Section: Spine) (Fig 1)mentioning
confidence: 92%
“…Serum cotinine and the frequency of bone diseases were positively and nonlinearly correlated. Fang, et al also reported that high serum cotinine levels significantly reduced lumbar BMD participants aged 30 years or older [30].…”
Section: Spine) (Fig 1)mentioning
confidence: 92%